Tilt of mean sea level along the Pacific coasts of North America and Japan. Issue 10 (20th October 2015) - Lin, Hongyang; Thompson, Keith R.; Huang, Jianliang; Véronneau, Marc
Abstract: The tilt of coastal mean sea level with respect to an equipotential surface is estimated using two fundamentally different approaches. The geodetic approach is based on tide gauge and GPS observations, and a model of the geoid. The ocean approach uses a high‐resolution, dynamically based ocean model to estimate mean dynamic topography. Along the Pacific coast of North America the two approaches give similar large‐scale profiles with a minimum at about 40°N and a maximum in the northern part of the Gulf of Alaska. Along the Pacific coast of Japan the geodetically determined coastal sea levels indicate an eastward drop of about 20 cm along the south coast and a further northward drop across Tsugaru Strait. Both of these features are reproduced by the ocean models. An analysis of the alongshore momentum balance suggests that alongshore wind stress acting over the inner shelf is the primary driver of the mean sea level profile along the coast of North America. Several large‐scale features are explained using arrested topographic wave theory. A similar momentum analysis, and an additional study of time variability of sea level and circulation, suggests that the Kuroshio is the main driver of the mean sea level tilt along the south coast of Japan. Discrepancies in the alongshore tilt of sea level estimated by the geodetic and ocean approaches along both coasts are discussed in terms of errors in the ocean and geoid models. Key Points: Geodetic and ocean methods give similar estimates of alongshore sea level tilt Alongshore wind stress is main driver along the Pacific coast of North America The Kuroshio is the main driver along the south coast of Japan